IMO-based novel adaptive dual-mode controller design for AGC investigation in different types of systems. Issue 1 (1st January 2020) - Mohapatra, Gayatri; Debnath, Manoj Kumar; Mohapatra, Krushna Keshab
Abstract: This article deals with a novel adaptive controller known as dual-mode proportional-integral-derivative (DMPID) controller employed to regulate the frequency of a three-area thermal-type interconnected system including nonlinearity in the form of generation rate constraints. The DMPID controller is tuned by ions motion optimization (IMO) technique to acquire its suitable gains by employing integral absolute error. The dynamic characteristics of the multi-area network with the above-mentioned control methodology are compared with the IMO-tuned PID controller and a previously published method such as bacteria foraging optimized integral controller to establish its supremacy. Further, case studies confirm the robustness of the proposed control approach while subjected to various system loadings, different positions of SLP and parameter variations. Also, the robustness of the recommended controller is validated in the presence of time delays. Finally, the proposed controller is applied in another multi-source model to prove its adaptability.